Genomics tools in microbial food safety. (August 2015) - Stasiewicz, Matthew J; den Bakker, Henk C; Wiedmann, Martin
Highlights: Whole genome sequencing has transformed foodborne disease surveillance. High-throughput bioinformatics tools will facilitate adoption of omics approaches. Omics approaches in food safety will soon move beyond bacterial genomics. Abstract : Genomics tools, and specifically whole-genome sequencing (WGS) methods, are rapidly transforming food safety, specifically through improved outbreak detection. In the U.S., whole genome sequencing of all human clinical Listeria monocytogenes isolates has been performed since 2013; isolates from foods and food processing plants obtained by regulatory agencies are also routinely characterized by WGS. Routine application of WGS appears to increase the number of listeriosis outbreaks that are detected and traced back to specific food sources. While rapidly improving WGS technologies have driven use of omics tools in food safety over the last 5–7 years, improved analytic methods will drive effective application of omics tools including genomics, transcriptomics, proteomics, and metabolomics over the next few years.